Nodulation in Andean and Mesoamerican cultivars of dry bean - Franco, Marília Caixeta; Cassini, Sérvio Túlio Alves; Oliveira, Valter Rodrigues; Vieira, Clibas; Tsai, Siu Mui (Pesquisa Agropecuaria Brasileira, 2002)
The objective of this work was to determine the capacity and specificity for nodulation in dry bean (Phaseolus vulgaris L.) cultivars, arising from Andean or Mesoamerican germplasm, inoculated with Rhizobium. The experiment was a factorial 14x3 in a randomized block design with fourteen dry bean cultivars and three strains of Rhizobium (R. etli KIM 5, R. etli CIAT 632 and R. tropici CIAT 899). Only five cultivars (WAF 15, WAF 7, Mineiro Precoce, WAF 6 and Antioquia 8), all from the Andean germplasm, demonstrated nodulation specificity. In relation to the nodules' dry weight, the values revealed significative difference when comparing the inoculation treatments of the Andean cultivars WAF 15, WAF 7, WAF 6 and Diacol Andino as well as the Mesoamerican cultivar Ouro Negro. None of the cultivars completely eliminated nodulation by the less compatible Rhizobium strains, but the differences in number of nodules per plant and the nodule dry weight among inoculation with the highly specific strains and the non-specific strains was 53 and 103 times greater, respectively. Considering all of the combinations of bean cultivars and Rhizobium strains, cultivar WAF 15 was the most responsive to nodulation and demonstrated superior growth and nodule number, while cultivar WAF 6 inoculated with CIAT 632 grew very little with practically no nodulation.